Effect of cold-water immersion on handgrip performance in rock climbers - Kodejška, J.; Baláš, J.; Draper, N. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine the effect of 2 cold-water-immersion (CWI) temperatures (15°C and 8°C) on repeat handgrip performance to failure. Methods: A total of 32 participants completed 3 intermittent trials to failure on a climbing-specific handgrip dynamometer on 3 laboratory visits. For each visit, a different recovery strategy was employed: passive (PAS) recovery, CWI at 8°C (CW8), or CWI at 15°C (CW15). The force time integral (FTI: time of contraction multiplied by the force of contraction) was determined to assess handgrip performance. Results: There was no significant difference between recovery strategies at the end of trial 1. In response to the PAS recovery strategy, there were 10% and 22% decreases in FTI in the second and third trials, respectively. The PAS recovery-strategy FTI values were lower than both CWI strategies for trials 2 and 3 (P<.05). FTI increased in the second trial (32% and 38%; P<.05) for both immersion strategies (CW8 and CW15, respectively) compared with trial 1. During the third trial, FTI was significantly higher for CW15 than CW8 (27% and 4% with respect to baseline trial; P<.05). Conclusions: The results suggest that CWI has potential performance advantages over PAS recovery for rock climbing. The data show that in events where multiple recoveries are required, 15°C CWI may be more beneficial for climbers than 8°C CWI. Future research should focus on the optimization of protocols for sport performance.